"Promotion tournament 2.0": Why local cadres expand health‐care provision in China. Issue 4 (4th August 2020) - Zhang, Yuxi
Abstract: Previous research has attributed the delayed welfare development in China to the government's traditional obsession with GDP growth target as the principal criteria for cadre promotion. Yet why has health‐care provision significantly expanded since the 2000s? This article argues that as central policies adjusted to incorporate health care as a priority, the cadre assessment system subsequently made it a "hard target, " and thus the competition for office has compelled local cadres to implement health‐care expansion. Apart from the importance of local leaders in policy change as the literature suggests, this article elaborates on the pivotal role of technical bureaucrats by innovatively introducing the "promotion tournament 2.0" model, which emphasizes the knowledge–power coalition between these political actors. By investigating the case of health‐care expansion, this article illustrates the local politics of policy change with various forms of data collected from semi‐structured interviews, newspaper archives, political documents, and official statistics.